DAMPAK PEMBINAAN KEMANDIRIAN SEBAGAI BENTUK PEMBEKALAN NARAPIDANA - Tampubolon, Gillbert R; Putera, Bintang Eriatama; Munir, Abdullahil; Warih, Wido Cepaka (Journal of Correctional Studies, 2024)
Development of independence towards prisoners aims to provide the ability of prisoners who are skilled in certain fields as provisions for returning to life in the community. This study aims to determine the effect of independence coaching on prisoners. This research uses qualitative methods with secondary data sources in the form of materials from the results of literature studies. The results of this study consistently show that self-reliance coaching has a significant positive impact on prisoners. These coaching programs provide opportunities for prisoners to develop skills and abilities that have the potential to increase their independence. Over time, inmates who participate in these programs tend to have specific skills that they can rely on in restarting their lives in the community. In addition, self-reliance coaching also helps prisoners to increase their self-confidence and motivation to succeed outside prison. With this research, the understanding of the important role of self-reliance coaching in the rehabilitation process of prisoners is clearer. By equipping prisoners with relevant skills and abilities, we may be able to reduce recidivism rates and reintegrate them into society more smoothly. These results provide a strong basis to continue developing more effective and sustainable self-reliance coaching programs in order to help inmates achieve personal success and social reintegration. Pembinaan kemandirian terhadap narapida bertujuan untuk memberikan kemampuan narapidana yang terampil di bidang tertentu sebagai bekal untuk kembali hidup di masyarakat. Penelitian ini bertujuan untuk mengetahui pengaruh pembinaan kemandirian tersebut terhadap narapidana. Penelitian ini menggunakan metode kualitatif dengan sumber data sekunder berupa bahan dari hasil studi Pustaka. Hasil dari penelitian ini secara konsisten menunjukkan bahwa pembinaan kemandirian memiliki dampak positif yang signifikan pada narapidana. Program-program pembinaan tersebut memberikan kesempatan bagi narapidana untuk mengembangkan keahlian dan kemampuan yang berpotensi untuk meningkatkan kemandirian mereka. Seiring berjalannya waktu, narapidana yang mengikuti program ini cenderung memiliki keterampilan khusus yang dapat mereka andalkan dalam memulai kembali kehidupan mereka di masyarakat. Selain itu, pembinaan kemandirian juga membantu narapidana dalam meningkatkan rasa